Data-to-music sonification and user engagement - Middleton, Jonathan; Hakulinen, Jaakko; Tiitinen, Katariina; Hella, Juho; Keskinen, Tuuli; Huuskonen, Pertti; Culver, Jeffrey; Linna, Juhani; Turunen, Markku; Ziat, Mounia; Raisamo, Roope (Frontiers in Big Data, 2023)
The process of transforming data into sounds for auditory display, provides unique userexperiences and new perspectives for analyzing and interpreting data. A research study for data transformation to sounds based on musical elements, called data-to-music sonification, reveals how musical characteristics can serve analytical purposes with enhanced user-engagement. An existing user engagement scale has been applied to measure engagement levels from three conditions within melodic, rhythmic, and chordal contexts. This paper reports findings from a user-engagement study with musical traits, and states the benefits and challenges of using musical characteristics in sonifications. The results can guide the design of future sonifications of multivariable data.